El Delito de Enriquecimiento Ilícito Afecta Gravemente al Estado y la Sociedad - Ochoa Calle, Julio José (2019)
The present thesis entitled: "The Crime of Illicit Enrichment Seriously Affects the State and the Society", is the result of the study of a problem that negatively affects the citizenship and that is related to the increase of illicit enrichment indexes. a correlation with the phenomenon of corruption entrenched in Ecuadorian society. The criminal law to have as one of its purposes to be in charge of the punitive control of criminality, which allows laws to emerge in the internal scope of a country to control the breach of the law, being necessary to indicate that the Organic Integral Penal Code is the current norm in Ecuador, where illicit enrichment is typified, as a crime that transgresses the efficiency of the public administration as a protected legal asset, in addition to harming other aspects such as health, education, housing, work, democracy, being the Ecuadorians who observe the violation of dormant rights after the commission of this illegal act. The Constitution of the Republic of Ecuador, specifically in article 3 numerals 1, 5, 8 establish as primary duties of the State, guarantee access to opportunities especially education, health, national development plan, eradicate poverty, achieve consolidate a country free of corruption; with a view to achieving good living, the supreme norm also establishes the 5 principle of proportionality of penalties with the damage caused to protected legal rights. Contributions that have served to corroborate the existence of the problem raised that concerns the benignity of the penalty determined for the crime of illicit enrichment, which disregards the principle of proportionality that is stipulated constitutionally and developed through the Organic Comprehensive Criminal Code, given the circumstances of increased rates of corruption and impunity; It is required that the legislator analyze a reform to this legal body to increase the penalty of the crime under study and thus control crime by forming a moral and ethical criterion in the public servants when administering the resources of the State.